2017
DOI: 10.1016/j.ebiom.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 Acts as a Specific Carrier of CpG DNA into Dendritic Cells and Activates Toll-like Receptor 9-mediated Adaptive Immunity

Abstract: CXCL14 is a primordial chemokine that plays multiple roles in tumor suppression, autoimmune arthritis, and obesity-associated insulin resistance. However, the underlying molecular mechanisms are unclear. Here, we show that CXCL14 transports various types of CpG oligodeoxynucleotide (ODN) into the endosomes and lysosomes of bone marrow-derived dendritic cells (DCs), thereby activating Toll-like receptor 9 (TLR9). A combination of CpG ODN (ODN2395) plus CXCL14 induced robust production of IL-12 p40 by wild-type,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…After tissue infiltration, IL-15 may help promote T-cell survival [30] and effector function by upregulating IFN-γ production [31] and decreasing IL-17A expression [32]. Priming of these effector Th1 responses may be aided by CXCL14 that is chemotactic for dendritic cells [33] and transports CpG oligodeoxynucleotides into endosomes for Toll-like receptor 9 stimulation [34], which subsequently leads to the development of Th1 responses [35]. This is consistent with the increased frequency of effector memory Th1 cells reported in CXCL14-transgenic mice [36].…”
Section: Discussionmentioning
confidence: 99%
“…After tissue infiltration, IL-15 may help promote T-cell survival [30] and effector function by upregulating IFN-γ production [31] and decreasing IL-17A expression [32]. Priming of these effector Th1 responses may be aided by CXCL14 that is chemotactic for dendritic cells [33] and transports CpG oligodeoxynucleotides into endosomes for Toll-like receptor 9 stimulation [34], which subsequently leads to the development of Th1 responses [35]. This is consistent with the increased frequency of effector memory Th1 cells reported in CXCL14-transgenic mice [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies have shown that CXCL14 may not directly affect CXCR4 [ 86 ]. Other studies have shown that the receptors for CXCL14 may be G-protein coupled receptor 85 (GPR85) [ 87 ], toll-like receptor (TLR)9 after the formation of a complex of CXCL14 with CpG oligodeoxynucleotide [ 88 ], and insulin-like growth factor I receptor (IGF-IR) [ 89 ].…”
Section: CXC Chemokines In Cancermentioning
confidence: 99%
“…Using the same end-point RT.PCR stratagem, we have reported a similar expression profile for the Ifnγ and inducible ligand genes Cxcl 9, Cxcl 10 and Cxcl 11 and its shared receptor gene Cxcr 3 to that reported in the infected brains of a rat model of HAT [ 34 ]. In contrast to the other Cxcl mRNAs, Cxcl 14 had a Stage 1 [7dpi↑] signature while a recent study found that the pleiotropic CXCL14 specifically binds to CpG DNA and activates TLR9 on macrophages, thereby inducing inflammatory cytokines [ 76 ]. This expression signature was compared ( Table 5 ) with a compilation profile of Ccl and Cxcl ligand genes expressed in infected rodent brains [ 3 ].…”
Section: Resultsmentioning
confidence: 99%